Serology for trachoma surveillance after cessation of mass drug administration. - Diana L Martin; Rhiannon Bid; Frank Sandi; E Brook Goodhew; Patrick A Massae; Augustin Lasway; Heiko Philippin; William Makupa; Sandra Molina; Martin J Holland; David C W Mabey; Chris Drakeley; et al. (PLoS Neglected Tropical Diseases)
Background Trachoma, caused by Chlamydia trachomatis (Ct), is the leading infectious cause of blindness worldwide. Yearly azithromycin mass drug administration (MDA) plays a central role in efforts to eliminate blinding trachoma as a public health problem. Programmatic decision-making is currently based on the prevalence of the clinical sign "trachomatous inflammation-follicular" (TF) in children. We sought to test alternative tools for trachoma surveillance based on serology in the 12-year cohort of Kahe Mpya, Rombo District, Tanzania, where ocular chlamydial infection was eliminated with azithromycin MDA by 2005. Methodology and principal findings The present study was a community-based cross-sectional survey in Kahe Mpya. Of 989 residents, 571 people aged 6 months to 87 years were enrolled: 58% of the total population and 73% of 1-9 year olds, the key WHO indicator age group. Participants were examined for TF, had conjunctival swabs collected for nucleic acid amplification test (NAAT)-based detection of Ct, and blood collected for analysis of antibodies to the Ct antigens pgp3 and CT694 by multiplex bead-based immunoassay. Seroconversion rate was used to estimate changes in the force of infection in a reversible catalytic model. No conjunctival swabs tested positive for Ct infection by NAAT. Among 1-9 year olds, TF prevalence was 6.5%, whereas only 3.5% were seropositive. Force of infection modelling indicated a 10-fold decrease in seroconversion rate at a time corresponding to MDA commencement. Without baseline serological data, the inferences we can make about antibody status before MDA and the longevity of the antibody response are limited, though our use of catalytic modelling overcomes some of these limitations. Conclusions/significance Serologic tests support NAAT findings of very low to zero prevalence of ocular Ct in this community and have potential to provide objective measures of transmission and useful surveillance tools for trachoma elimination programs.